Mophological and neurohistological characterization of cerebellum with different rostro-caudal axis orientations of selected local freshwater fishes / Shamiza Ahmad Shaharudin - Ahmad Shaharudin, Shamiza (2012)
Compared to the rest of the brain, the cerebellum is a small but outstanding structure which is present in all vertebrates. It is a dorsally located metencephalic structure of the rhombencephalon and plays important roles in movements. As in other vertebrates, the cerebellum is expected to be regulating the control of fish movements; related to maintenance of posture and balance, and coordinated movements. Emphasis of the study was on the gross morphology and neurohistology of the cerebellum of selected freshwater fishes. Preliminary studies revealed the existence of different cerebellar orientations in fishes, either rostrally or caudally directed. Four Malaysian freshwater fish species, with two species representing each cerebellar orientation, were looked at as part of an ongoing study in developing Malaysian freshwater fish central nervous system database. Keli (Clarias sp.) and baung (Mystus nemurus) represented fish with rostrally oriented cerebellum, while tilapia (Oreochromis sp.) and jelawat (Leptobarbus hoeveni) represented fish with caudally oriented cerebellum. The shape of the body and features of each fish were correlated to the cerebellar orientation. Both keli and baung, which have rostrally directed cerebellum, demonstrated the same ‘torpedo-shaped’ body form; while jelawat and tilapia with caudally directed cerebellum displayed the same compressed body shape. The external morphological features of the cerebellum of these fishes were observed and measured. Each cerebellum exhibited morphological features common to specific cerebellar orientation. For keli’s and baung’s rostrally oriented cerebellum, the median-longitudinal sulcus and gyrus were found on their cerebellar surfaces respectively; while for tilapia’s and jelawat’s caudally oriented cerebellum, neither sulcus nor gyrus was found. Each fish cerebellum was histologically shown to be made up of mostly cortex area. Stained with H&E and Nissl, the architecture of cerebellar cortex in those fishes appeared similar, i.e. consisting of molecular layer at the outermost, followed by Purkinje and granular neuronal layers towards the inner area. The granular layer made up the inner region of densely packed stained neuronal somas in cerebellum of these fishes, while the outer region was not intensely stained. Transverse and longitudinal sections of cerebellar tissue of each fish portrayed unique structure of the innermost area. Transverse sections of keli’s, baung’s and jelawat’s cerebellum showed a ‘butterfly like’ pattern of the innermost area. In contrast, a ‘dome like’ pattern of innermost area pointing dorsally was observed in tilapia’s cerebellum transverse sections. Longitudinal cerebellum sections stained with Thionin staining showed fibers in the white matter, which existed within the core portion of the innermost area. These fibers could be mossy and climbing fibers as had been reported in higher vertebrates. It is also possible that cerebellum of fish represents one primitive convolution / folium of higher vertebrate cerebellum. Architectural 3D details of the unique pattern of cerebellar granular layer and possible correlation to physiological cerebellar functions should be further studied.